Analisis Potensi Budaya di Provinsi Maluku dengan Pendekatan Statistika Spasial - Yudistira; Loklomin, Samsul Bahri (Journal of Mathematics, Computations and Statistics, 2023)
Culture advancement as part of a sustainable national development, needs to be supported bydata and information about factual conditions of cultural potential at national, provincial and districtlevel. However, until now there have not been many quantitative studies with subject related to culture.This research was one of efforts made to enrich quantitative studies related to cultural studies, as well asimplemented such knowledges about spatial statistics for cultural data and information. The main methodused in this research was secondary data analysis from various sources related to cultural potential inMaluku Province, which was available down to district level. Some spatial statistic measures used areGlobal Moran index, Local Indicators for Spatial Association (LISA), as well as spatial cross-correlation,which are applied to all variables related to cultural potential in this research. The results of analysisgenerally didn’t show statistically significant of spatial autocorrelation for each of these culturalpotentials. Nonetheless, there were several important results conducted in this research, that would beinteresting to note as basis for formulating cultural development policies in Maluku Province.